Three reasons to trust on the "law of trust" (La legge della fiducia) - Pérez Luño, Antonio Enrique (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2022)
This article is part of the monographic section "Derecho y confianza” Professor Tommaso Greco’s book La legge della fiducia stands out for the originality and timeliness of its approach, since it represents a change of direction in studies on the meaning of legislation at the present time. Faced with the tendency, predominant in recent years, to allude to the crisis of the law, Professor Greco defends trust in the law, as long as it is a law worthy of trust. There are three reasons that make the theoretical-legal proposal that Tommaso Greco exposes us in his book worthy of intellectual trust. The firstrefers to the past. It deals with the vexata quaestio of whether the law should be based on anthropological optimism or pessimism. The second is part of the present due to its suitability to strengthen the guarantee of two basic values that sustain democratic societies: civic education and legal certainty. The third has a vocation for the future, since it concerns the role of the law in the technological society and the projections of Artificial Intelligence in legislative production.